From Tradition to Innovation: Enhancing Village MSMEs’ Business Sustainability Through Digital Literacy and Community Engagement" - Putri, Elsa Aryusi Kusuma Dwi; Balqish, Nisrina Fauziah; Lestari, Yunita Dwi; Ambarwati, Ardita Putri; Tricana, Deny Wahyu (Pena Dimas: Jurnal Pengabdian Masyarakat, 2025)
Community Service Program represents the practical implementation of the Tri Dharma Perguruan Tinggi in the field of community service. The activity conducted in Ngrogung Village, Ngebel District, aimed to address challenges faced by Micro, Small, and Medium Enterprises (MSMEs), including the limited utilization of digital technology, lack of product development leading to weak competitiveness, and licensing barriers that hindered business growth. The program employed the Asset-Based Community Development (ABCD) approach, emphasizing the utilization of local assets such as community skills, social networks, natural resources, and MSME experience. Through mentoring and empowerment activities, the program sought to strengthen existing capacities to enable MSMEs to grow independently and sustainably. The results demonstrated improved understanding among MSME participants regarding innovation and digital transformation. They successfully adopted digital tools such as WhatsApp Business, Instagram, Facebook Marketplace, Canva, and Google Sites for marketing, product promotion, and online catalog development. Additionally, several MSME actors obtained home industry food business permits (PIRT), enhancing their legitimacy and competitiveness. The outcomes indicated substantial progress in digital literacy, product branding, and market expansion, with participants showing improved entrepreneurial skills, more attractive product packaging, and early adoption of digital payment systems. This initiative has not only fostered individual capacity development but also promoted collective awareness of innovation as a key driver of sustainable rural economic growth. Overall, the program contributes directly to achieving three key Sustainable Development Goals (SDGs): SDG 4 (Quality Education) through digital training and capacity building, SDG 8 (Decent Work and Economic Growth) by encouraging sustainable entrepreneurship and enhancing rural economic productivity, and SDG 9 (Industry, Innovation, and Infrastructure) by fostering innovation and strengthening digital business ecosystems within local communities.